Sosialisasi Bahaya Riba Pada Masyarakat Pesantren Miftahussa’adah Desa Nusa Makmur, Kecamatan Air Kumbang - Havis Aravik (AKM, 2020)
This dedication is the socialization of the dangers of riba to the Miftahussa'adah Islamic Boarding School in Nusa Makmur village, Kec. Air Kumbang. With the aim of knowing the extent of knowledge and understanding of the dangers of riba, so that it can be implemented in everyday life. The method used in this procurement is by way of exposure to material and interactive question and answer with the community. The results of devotion show that direct socialization to the community has a very significant impact on religious understanding and increases the enthusiasm of the community to study the economy and banking in Islam further. The results of community understanding can be seen in the form of people's desire to avoid all forms of riba in the form of a very simple loan and others. Furthermore, increasing public understanding of the dangers of usury, will foster more interest in practicing economics in Islam so that it gets maslahah and falah in his life.